Characterisation of secondary phases in Ni-base superalloy Rene 65. Issue 13 (2nd September 2018) - Wojcik, Tomasz; Rath, Markus; Kozeschnik, Ernst
ABSTRACT: The Ni-base superalloy Rene 65 is a newly introduced cast and wrought alloy, used for turbine disc applications in aero-engines. The fine-grained and γ ′-strengthened alloy was developed to increase service temperatures up to over 700°C and therefore, enhance the efficiency of aerospace turbines. In this work, the phases occurring in the as-received material as well as after continuous cooling experiments are characterised by transmission electron microscopy (TEM). In the as-received material, a tri-modal γ ′ size distribution is found, ranging from a few nanometres up to approx. 5 µm. In addition, borides are found preferentially at grain boundaries with a size of approx. 1 µm. For different cooling rates, a change in morphology and size distribution of γ ′ precipitates is found. This is part of a thematic issue on Nanoscale Materials Characterisation and Modeling by Advances Microscopy Methods - EUROMAT.